Relationship between personal moral philosophy and ethical decision making among hotel human resource practitioners in Klang Valley, Malaysia - Chan, Ling Meng (2012)
The objectives of this study were: 1) to describe the components of ethical decision making and personal moral philosophy, 2) to determine differences between male and female HR practitioners in the components of ethical decision making, 3) to determine the relationship of idealism and relativism on the components of ethical decision making among HR practitioners, and 4) to determine the relative influence of idealism and relativism on the components of ethical decision making among HR practitioners. This study adopted Ex – Post Factor Correlational design. The Ethics Positions Questionnaires (EPQ) and Hospitality Ethical Scenarios Questionnaires assessed respondents’ personal moral philosophy and ethical decision making respectively. The snowball sampling technique was used in the study with the target respondents of human resources practitioners in hotel industry. Internal consistency of the EPQ’s idealism and relativism subscales and the Hospitality Ethical Scenarios Questionnaires were .860, .821, and .700 respectively. Findings from the study showed: 1) respondents scored the highest score in their ethical behaviour (M = 20.66; SD = 2.03), while they have the lowest scores in ethical intention (M = 10.73; SD = 3.27). Respondents reported higher idealism scores (M = 37.64; SD =7.10) than relativism score (M = 28.80; SD = 7.12), suggesting that highly idealistic respondents tended to make stricter ethical decision; 2) there are significant differences (p = 0.001) between males (M = 66.06; SD = 6.50) and female (M = 68.26; SD = 3.62)in ethical behaviour (t = -2.27), ethical awareness (t = -1.67) and ethical intention (t = -3.56) respectively suggested that female tended to hold more firmly on ethical values compare to male, even though the effect size is small; 3) there was positive relationship between idealism with ethical behaviour (r = .777), ethical awareness (r = .654) and ethical intention (r = .546) respectively while relativism was found to have negative relationship with ethical behaviour (r = -.689), ethical awareness (r = -.754) and ethical intention (r = -.615) respectively. This suggested that highly idealistic but low relativist respondents tended to have higher of ethical decision making; and 4) ethical behaviour (AR2 = .366) has the stronger contribution in analysis, idealistic human resources practitioners tended to engaging in ethically right actions when they encounter ethical dilemmas. As conclusion, ethical decision making: ethical behaviour, ethical awareness and ethical intention assist human resource practitioners, especially female in making an appropriate decisions in ethical dilemma, while their male counterparts are more focus on the result oriented. Furthermore, high idealist human resource practitioners always avoid inflicting harmful decisions on other, while low relativist human resources practitioners are more stress on the importance of ethical values when making ethical decisions. Idealist human resource practitioners always behave ethically right when they making ethical decision.